Micro-interventional pre-treatment for nucleus disassembly in the setting of non-cavitating sonic lensectomy: real-world evidence study in 512 cases - Sean Ianchulev; Elizabeth Yeu; Edward H. Hu; Gautam Kamthan; Seth Pantanelli; Paul Singh; Farrell Tyson (BMC Ophthalmology)
Abstract Objectives To investigate the effect of adjunct micro-interventional pre-treatment for nucleus disassembly on the surgical efficiency of non-cavitating lensectomy during cataract surgery. Methods and analysis 12 surgeons performed 512 consecutive cataract extractions using a sonic cavitation-free lensectomy with or without adjunct pre-treatment for nucleus disassembly. There were 2 interventional arms including (1) lensectomy without adjunct pre-treatment and (2) lensectomy with micro-interventional miLOOP pre-treatment. Results Successful lensectomy was achieved in all eyes using cavitation-free sonic lensectomy. Average baseline cataract density was 2.28 and 2.39 in the three groups, respectively. Compared to no pre-treatment, nucleus evacuation time was 24% (p = < 0.001) faster with micro-interventional nucleus disassembly. Irrigation/aspiration (I/A) time was 14% faster with the micro-interventional pre-treatment (p = < 0.001). Irrigation fluid use was 24% less with micro-interventional. There was a low rate of capsular tear of 1 case across 512 cases with no other unanticipated complications. Conclusion Micro-interventional pre-treatment for nucleus disassembly was associated with improved lensectomy time and fluidic efficiency compared to no pre-treatment. Non-cavitating lensectomy with the miCOR lens pen achieved effective fragmentation and extraction in all grades of cataract.